1996
DOI: 10.1007/bf03011908
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia for Caesarean section in a patient with a cervical arteriovenous malformation

Abstract: The safe outcome of spinal anaesthesia for our patient is encouraging. The presence of spinal cord AVM at the cervical region is not an absolute contraindication to spinal anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
(2 reference statements)
0
19
0
Order By: Relevance
“…Rapid epidural administration of large volumes of drug should be avoided to avoid increase in increased ICP. [3738]…”
Section: Parturient With Brain Tumormentioning
confidence: 99%
“…Rapid epidural administration of large volumes of drug should be avoided to avoid increase in increased ICP. [3738]…”
Section: Parturient With Brain Tumormentioning
confidence: 99%
“…37 Therefore, much attention is focused on avoiding the increases in venous pressure which occur with uterine contractions and valsalva maneuvres. 39 …”
Section: Cerebral Avmsmentioning
confidence: 99%
“…52 It has been suggested that even distant SAVMs may cause a change in venous drainage locally at the site of injection, thus altering the A-V gradient. 39 Conversely, some argue that the increase in pressure following epidural injection is only transient, and in the rare situation of a patient who has sustained a spinal injury from a distant SAVM bleed, there may even be some benefits of an epidural in managing autonomic hyperreflexia perioperatively, thus avoiding the need to use suxamethonium with the risk of associated hyperkalemia. 37 The successful management of a patient with a cervical SAVM undergoing Cesarean delivery using spinal anesthesia has been described.…”
Section: Respiratory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Ong et al (2) suggests that spinal anesthesia can be done for patients with arteriovenous malformation. The experience of others, and our own recent case, suggest that neuraxial anesthesia should be considered contraindicated in the presence of an AVM.…”
Section: Spinal Subdural Hematoma: a Pre-eclamptic Patient With A Spimentioning
confidence: 99%